(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The goal of this study is to make supply chain activity more sustainable by lowering the likelihood of disruption during pandemic COVID 19. Two subcategories of the multifaceted supply chain risks are operational risks and disruptive risks. Disruption risks directly affect how the supply chain network is constructed as a result of the temporary suspension of transportation linkages between various industries, vendors, and distribution centres. Downstream in the supply chain, the ensuing supply shortfall and delivery difficulties have a negative cascade effect that lowers performance in terms of productivity, revenue, and service quality. This study looks into the impact of the COVID-19 pandemic on supply chain management activities. It tries to appreciate the challenges that develop during a pandemic and recognised experiences in